Mrs Humphry Ward and Greenian Philosophy - Loader, Helen. author. aut Link
XV, 281 p. 3 illus., 1 illus. in color.
Keywords: This book examines Mary Ward’s distinctive insight into late-Victorian and Edwardian society as a famous writer and reformer, who was inspired by the philosopher and British idealist, Thomas Hill Green. As a talented woman who had studied among Oxford University intellectuals in the 1870s, and the granddaughter of Dr Arnold of Rugby, Mrs Humphry Ward (as she was best known) was in a unique position to participate in the debates, issues and events that shaped her generation; religious doubt and Christianity, educational reforms, socialism, women’s suffrage and the First World War. Helen Loader examines a range of biographical sources, alongside Mary Ward’s writings and social reform activities, to demonstrate how she expressed and engaged with Greenian idealism, both in theory and practice, and made a significant contribution to British Society.